Dynamic model of ecotourism management in Mount Rinjani National Park. (December 2019) - Sadikin, P N; Mulatsih, S; Pramudya, B; Arifin, H S
Abstract: Mount Rinjani National Park (MNRP) in Indonesia which is popular as one of ecotourism destination has facing problems including forest destruction which then becomes critical degraded lands, watersheds damaged, decreased river water, garbage due to lack of awareness. This study aimed to analyze the dynamic model to simplify and simulate the behavior of the ecotourism management system. The method used was powersim dynamic system software based on the scenarios compiling from controlled inputs: (1) the number of tourists, (2) the ticket price, (3) carrying capacity. The simulation of the first scenario for year 2015 to 2030 shows the total tourists in 2015 exceed the carrying capacity of 42, 525 people per year. On the first-stage ticket of IDR 384, 000, the number of tourists increased in 2018, reached 52, 268 people and in 2030 reached 57, 268 people. The second scenario applied a higher ticket price policy based on Willingness to Pay (WTP). The increasing ticket prices in stages up to IDR 650, 000 for international tourists and IDR 45, 000 for domestic tourists, and in 2030 the number of tourists will decline around 15, 013 people.